البيئة الاجتماعية والمهنية للمراسل الصحفي بالجنوب الجزائري - سلمان، إسماعيل, رحومة، عبد العالي (جامعة الوادي University of eloued, 2018)
"ملخص الدراسة هدفت الدراسة إلى التعرف على أثر البيئة الاجتماعية والمهنية للمراسلين الصحفيين في القنوات الجزائرية بالجنوب الجزائري على أدائهم المهني وتقديمهم للرسالة الإعلامية واعتمدت الدراسة على المنهج المسحي، عن طريق أسلوب المسح لعينة متكونة من 32 مراسلا للقنوات التلفزيونية موزعين عبر جميع ولايات الجنوب الجزائري، باستعمال أداة الاستبيان في جمع البيانات، وتوصلت الدراسة إلى العديد من النتائج أهمها: - أغلب المراسلين المعتمدين يمثلون أكبر القنوات الخاصة في المشهد الإعلامي في الجزائري. - العنصر النسوي شبه منعدم نظرا للعادات والتقاليد وطبيعة المجتمع، إضافة إلى صعوبة العمل في مجال السمعي البصري. - يتمركز اغلب المراسلين الصحفيين في القنوات الخاصة في مقر سكنهم في عاصمة الولاية، لأنها محرك ومصدر رئيسي للأحداث. - من أبرز الصعوبات المادية التي تواجه المراسل في القنوات التلفزيونية الخاصة ضعف الراتب او المنحة التي تقدم مقابل تقديم ونقل الأخبار والمعلومات وهو ما جعل الكثير منهم يفكر في الاستقالة او الخروج من المهنة نهائيا. - ساهم العمل المتواصل في تتبع الأحداث لحظة وقوعها وعدم الاستقرار والضعظ اليومي في التأثير على صحة ومردودية المراسل الصحفي. - لا يوجد رضا من قبل المراسلين على الأداء المهني لتراكم عديد الأسباب منها قلة الإمكانيات وضعف الراتب، وانعدام وسائل النقل وغياب التحفيزات والامتيازات وعدم توفير المعدات والوسائل وضعف شبكات الإرسال. الكلمات المفتاحية: القائم بالاتصال- المراسل الصحفي- القنوات الخاصة- البيئة الاجتماعية والمهنية، الأداء المهني. " "Study Summary The study aimed to identify the impact of the social and professional environment of the journalists in the Algerian channels in the southern Algerian on their professional performance and to submit them to the media message. The study was based on the survey method by surveying a sample of 32 TV channel correspondents distributed across all southern states of Algeria, Data collection, and the study reached several results, the most important of which are: Most accredited correspondents represent the largest private channels in the Algerian media scene. - The female component is almost non-existent due to customs and traditions and the nature of society, in addition to the difficulty of working in the field of audiovisual. - Most journalists are based on private channels at their residence in the state capital, as they are a major engine and source of events - One of the most difficult physical difficulties faced by the reporter in the private television channels is the salary or grant that is offered in return for the provision of news and information, which made many of them thinking of resigning or get out of the profession permanently. - Continuous action in tracking events at the moment of occurrence, instability and daily stress contributed to the impact on the health and profitability of the reporter. - There is no satisfaction from the correspondents on the professional performance of the accumulation of many reasons, including lack of possibilities and poor salary, lack of transport and the absence of incentives and privileges and the lack of equipment and equipment and poor transmission networks. Keywords: contact person - reporter - private channels - social and professional environment, professional performance "
دراسة ميدانية لعينة من مراسلي القنوات التلفزيونية الخاصة
مذكرة ماستر في الإعلام والإتصال تخصص سمعي بصري
Keywords: المراسل الصحفي، القنوات الخاصة، الأداء المهني.; Journaliste, chaînes privées, performance professionnelle.; Journalist, private channels, professional performance.